Kultur Antera Hasil Persilangan Padi Lokal Beras Hitam dengan Varietas Budidaya (Fatmawati dan Inpari 13) - Azmi, Yudia; Purwoko, Bambang Sapta; Saraswati Dewi, Iswari; Syukur, Muhamad; Suhartini, dan Tintin (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2017)
ABSTRAK Development of black rice is quite rapid in Indonesia. The objective of this study was to obtain doubled haploid black rice lines with good agronomic characters through anther culture. Materials used in this experiment were 6 F1 derived from black rice landrace (Melik) and two cultivated varieties (Inpari 13 and Fatmawati): Melik/Inpari13//Inpari13, Melik / Inpari13// Melik, Melik/Fatmawati //Fatmawati///Fatmawati, Melik/ Fatmawati//Fatmawati// /Fatmawati, Melik/Fatmawati, and Melik/Fatmawati//Melik. The experiment was performed using a completely randomized design consisting of 12 replications. An experimental unit was a petri dish containing ± 150 anthers. Results of the anther culture varied widely between crosses. Crosses Melik/Inpari13//Melik, Melik/Fatmawati//Melik, and Melik/Inpari13 //Inpari13 showed the best response on callus induction and plant regeneration compared to the other crosses. Melik / Inpari13 // Melik produced the highest number of acclimatized plants, the highest number and percentage of doubled haploid: 63 plants, 42 plants and 91.3% respectively. The highest number of doubled haploid having black aleuron layer were obtained by Melik/Inpari13//Melik and Melik/Fatmawati//Melik.Keywords: anther culture, black rice, doubled haploid, regeneration